2015
DOI: 10.3758/s13414-015-1043-x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for surface organization in Kanizsa configurations during continuous flash suppression

Abstract: Does one need to be aware of a visual stimulus for it to be perceptually organized into a coherent whole? The answer to this question regarding the interplay between Gestalts and visual awareness remains unclear. Using interocular suppression as the paradigm for rendering stimuli invisible, conflicting evidence has been obtained as to whether the traditional Kanizsa surface is constructed during interocular suppression. While Sobel and Blake (2003) and Harris, Schwarzkopf, Song, Bahrami, and Rees (2011) failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 61 publications
(83 reference statements)
3
27
0
Order By: Relevance
“…This view is supported by several recent studies; for instance, Mudrik and colleagues (2011) have demonstrated that relationships between fore-ground objects and background scenes can be processed without awareness (Mudrik & Koch, 2013; for a review, see Mudrik, Faivre, & Koch, 2014). Furthermore, intact Kanizsa figures, which integrate to form illusory contours, break from suppression faster than nonintact figures (Wang et al, 2012, but see Moors et al, 2015). With respect to more complex stimuli, as stated previously, upright faces break from suppression faster than inverted faces, with inversion known to disrupt holistic processing (Jiang et al, 2007;Stein et al, 2012;Zhou, Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This view is supported by several recent studies; for instance, Mudrik and colleagues (2011) have demonstrated that relationships between fore-ground objects and background scenes can be processed without awareness (Mudrik & Koch, 2013; for a review, see Mudrik, Faivre, & Koch, 2014). Furthermore, intact Kanizsa figures, which integrate to form illusory contours, break from suppression faster than nonintact figures (Wang et al, 2012, but see Moors et al, 2015). With respect to more complex stimuli, as stated previously, upright faces break from suppression faster than inverted faces, with inversion known to disrupt holistic processing (Jiang et al, 2007;Stein et al, 2012;Zhou, Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 63%
“…This prediction is further supported by studies showing that the extraction of global image features is possible without awareness (Kaunitz, Fracasso, Lingnau, & Melcher, 2013;Wang, Weng, & He, 2012). Specifically, intact illusory Kanisza figures break from suppression faster than their nonillusory, misaligned counterparts (Wang et al, 2012; but see Moors, Wagemans, van Ee, & de-Wit, 2015, for an alternative interpretation). By the same token, moving dot ensembles containing coherent radial motion were more accurately detected in CFS than dot ensembles containing random motion (Kaunitz et al, 2013).…”
Section: Introductionsupporting
confidence: 61%
“…The collinearity of edges and the thereby inferred surface may be processed even while the stimulus is suppressed from awareness–this may in turn produce an attentional signal that causes the stimulus to break suppression. Recent experiments that tested a range of visual control stimuli under CFS suggest that low-level properties of the stimulus determine the time it takes to break suppression [ 51 ]. Such stimulus-dependent effects are also plausible because attentional processing can occur without awareness of the stimulus [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…1). Some scholars (Hesselmann et al, 2016;Moors et al, 2016b) have used a setup in which two displays that are set opposite to each other, project stimulus to the left and right eye respectively via two mirrors. More details of our mirror stereoscope setup can be found from the toolbox project page.…”
Section: Program Descriptionmentioning
confidence: 99%